2016
DOI: 10.17116/neiro2016806115-117
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and treatment of postoperative epidural scar adhesions

Abstract: Postoperative epidural scar adhesions remain one of the most frequent late complications of microdiscectomy, which deteriorates the overall outcome in treatment of herniated lumbosacral discs. Despite a large number of conservative and surgical treatment options for epidural scar adhesions, the treatment outcome not always satisfies the patient and doctor. The review's aim was to systematize the available data on this complication and to facilitate the choice of appropriate tactics for its treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…For the prevention of EF progression, the most commonly used and recommended technique that causes less tissue damage is microsurgery [8]. Given that microsurgery leads to less dead space in the paraspinal region and epidural area, it is likely to result in less scar tissue.…”
Section: Resultsmentioning
confidence: 99%
“…For the prevention of EF progression, the most commonly used and recommended technique that causes less tissue damage is microsurgery [8]. Given that microsurgery leads to less dead space in the paraspinal region and epidural area, it is likely to result in less scar tissue.…”
Section: Resultsmentioning
confidence: 99%
“…The methods used in the treatment of chronic lumbar radicular pain include medical analgesic drugs, centrally acting drugs (e.g., duloxetine and pregabalin, physical therapy and rehabilitation, lumbar epidural and transforaminal epidural steroid injections, dorsal root ganglion (DRG) pulse radiofrequency, and epidural lysis) [7]. A number of studies demonstrated the efficacy of epidural neuroplasty in the treatment of patients with persistent, chronic low back pain [8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Conservative treatment of symptomatic EF encompasses patient education, physiotherapy, analgesia with non-steroidal anti-inflammatory drugs, and injections of corticosteroid and local anesthetic agents. 86,87 Moreover, as recently reviewed, spinal cord stimulation has produced encouraging results in patients with FBSS. 88 EF symptoms refractory to conservative therapy can subsequently be addressed using two key approaches, namely fluid administration and mechanical release.…”
Section: Treatment Strategies (Conservative Interventional and Operat...mentioning
confidence: 99%